AgileTalk: A Conversational Virtual Reality Synthetic Platform for Training in Agile Processes - Campo, Marcelo Ricardo (2021)
In this article, the main motivations and conceptual basis of using chatbot-based technology as the platform to support education and training on agile development are presented, using ScrumTalk as an example. ScrumTalk is a prototype of an intelligent conversational core for the AgileTalk platform under development for an Intelligent Synthetic Agile Software Development Environment. AgileTalk represents an ambitious evolution of Virtual Scrum (a Virtual Reality-based platform for Scrum training we developed some years ago) towards a synthetic 3D conversational-based full-fledged process training and development environment…